COMMUNITY SERVICE, EDUCATION, SELF-CARE OF EPISIOTOMY WOUNDS AND MOTHER-CHILD HIGH-RISK SCREENING THROUGH A LOCAL WISDOM APPROACH IN MEDAN TUNTUNGAN DISTRICT - Fistaqul Isnaini; Willhelmina Wahara; Julaiha Siregar (Cattleya Darmaya Fortuna, 2025)
The postpartum period and the early period of child growth are a very crucial transition phase as well as vulnerable for the health of the mother and baby. One of the medical interventions that is often carried out in the normal delivery process is an episiotomy, which is the use of the perineal area to widen the birth canal. Although medically intended, episiotomy wounds require intensive and hygienic postpartum care. Problems arise when postpartum mothers return to the home environment, where knowledge of wound self-care is often still very limited, compounded by the fear of touching the wound area as well as the lack of access to practical information. The program will be held on June 19, 2025 with interactive counseling methods and group discussions. The results of the evaluation showed that there was an improvement in the mother's skills in performing wound care independently and accelerating the detection of health risks through methods relevant to the local culture. This education is expected to help reduce the number of postpartum complications (such as wound infections) and increase the effectiveness of the maternal-child health screening system.